Relação entre estresse oxidativo e nível de atividade física em pacientes com apneia obstrutiva do sono - CAMPELO, Sinara Mendes (2022)
Introduction: Physical activity (PA) has been adopted as a form of treatment for obstructive sleep apnea (OSA), since it activates adaptive responses that favor the gene expression of antioxidant defense systems, regulating oxidative stress (EO). Objective:Evaluate the level of physical activity, oxidative stress levels, risks of developing the disease and sleep quality of patients with obstructive sleep apnea and compare with the control group. Methods: Cross-sectional study, carried out with two groups: GAOS (n = 12) and CG (n = 17). All answered the Berlin Questionnaire (BQ), the Pittsburgh Sleep Quality Index (PSQI), the International Physical Activity Questionnaire (IPAQ) and blood was collected to determine the rates of Malondialdehyde (MDA) and Glutathione (GSH). Statistical analysis was performed using SPSS Software 20.0, with significance set at 5% (p < 0.05). Results: The GAOS has a higher body mass index (BMI) (33.20 ± 4.73; CG: 27.99 ± 6.03 kg ∕ m²), greater neck circumference (40.20 ± 3.65; CG : 36.41 ± 4.03 in cm) and abdominal (106.45 ± 11.67; CG: 94.64 ± 12.85 in cm), higher levels of MDA (5.62 ± 1.98; CG: 0.94 ± 0.76 in nmol ∕ mL) and 100% risk for OSA compared to CG. There was no significant difference between groups in GSH levels (GAOS: 120.99 ± 27.75; CG: 119.44 ± 13.80 µmol / g Hb), IPAQ score (GAOS: 3785.5 ± 3554, 5; CG: 2468.6 ± 2245.5 in MET-min ∕ week) and PSQI categories (p = 0.408). Conclusion: Both groups are physically active and have poor sleep quality. However, only GAOS have higher BMI, greater cervical and abdominal circumference measures, high risk of developing a disease due to BQ, corroborating the clinical findings of patients with OSA, with the highest levels of MDA being identified as a potential clinical marker in this population.